Classification of retinal ganglion cells in the southern hemisphere lamprey Geotria australis (Cyclostomata). Issue 4 (15th January 2014) - Fletcher, Lee Norman; Coimbra, João Paulo; Rodger, Jennifer; Potter, Ian C.; Gill, Howard S.; Dunlop, Sarah A.; Collin, Shaun P.
ABSRACT Lampreys are one of two extant representatives of the earliest group of vertebrates, the agnathans or jawless fishes. The single species of the southern hemisphere lamprey family Geotriidae, Geotria australis, possesses the potential for pentachromatic color discrimination opposed to the mono‐ or dichromacy found in other lampreys. However, little is known of the retinal ganglion cell types that contribute to visual processing in G. australis. A quantitative morphological approach was used to distinguish and describe retinal ganglion cell types in G. australis. The morphology of retinal ganglion cells was revealed by retrograde biocytin labeling from the optic disc. Cells were digitally reconstructed, and somatic area and position and dendritic field size, density, tortuosity, and stratification were subjected to quantitative morphometric analyses. Cluster analysis, in conjunction with similarity profile analysis (SIMPROF), statistically identified five discrete monostratified retinal ganglion cell types, one of which may comprise two subtypes. Two bistratified types were identified separately, including a biplexiform and a bistratified subtype. The use of cluster analysis with SIMPROF provided a robust statistical technique for objectively identifying cell types whose characteristics were similar and significantly different from those of other types and thus provides an objective resolution of the problems posed by "lumpers vs. splitters" when designating cell types. The diversity of retinal ganglion cells suggests that visual information in the lamprey G. australis is processed in parallel streams, as in gnathostomes. These findings, together with the results of previous studies, indicate that the visual system of the lamprey G. australis represents the upper limit of visual complexity in extant agnathans. J. Comp. Neurol. 522:750–771, 2014. © 2013 Wiley Periodicals, Inc.